1) x1=0; x2=-2/3.
2) x1=5; x2=-9.
3) x1=5; x2= 2 2/3.
Объяснение:
1) 3х²+2х=0;
x(3x+2)=0;
x1=0;
3x=-2;
x2=-2/3.
***
2)х²+4х-45=0;
a=1; b=4; c=-45;
D=b²-4ac=4²-4*1*(-45)=16+180=196;
D=196>0 - два корня.
х1=(-b+√D)/2a=(-4+14)/2*1 10/2=5;
x2=(-b-√D)/2a=(-4-14)/2=-18/2=-9.
3) 3х²-7х-40=0;
a=3; b=-7; c= -40.
D=b²-4ac=(-7)²-4*3*(-40)=49+480=529;
D=529>0 - два корня.
х1= (-b+√D)/2a=(-(-7)+√529)/2*3=(7+23)/6=30/6=5;
x2=(-b-√D)/2a=(-(-7)-√529)/2*3=(7-23)/6=16/6=2 2/3.
1) x1=0; x2=-2/3.
2) x1=5; x2=-9.
3) x1=5; x2= 2 2/3.
Объяснение:
1) 3х²+2х=0;
x(3x+2)=0;
x1=0;
3x=-2;
x2=-2/3.
***
2)х²+4х-45=0;
a=1; b=4; c=-45;
D=b²-4ac=4²-4*1*(-45)=16+180=196;
D=196>0 - два корня.
х1=(-b+√D)/2a=(-4+14)/2*1 10/2=5;
x2=(-b-√D)/2a=(-4-14)/2=-18/2=-9.
***
3) 3х²-7х-40=0;
a=3; b=-7; c= -40.
D=b²-4ac=(-7)²-4*3*(-40)=49+480=529;
D=529>0 - два корня.
х1= (-b+√D)/2a=(-(-7)+√529)/2*3=(7+23)/6=30/6=5;
x2=(-b-√D)/2a=(-(-7)-√529)/2*3=(7-23)/6=16/6=2 2/3.